PENGARUH DISIPLIN DAN KECAKAPAN KERJA TERHADAP KUALITAS PELAYANAN SEKRETARIAT DAERAH - Diding Bajuri; Rewind Tri Fazardo (Universitas Bandar Lampung (UBL), 2023)
The problems in this study are: (1) Is there an influence of discipline on service quality at the Regional Secretariat of Majalengka Regency, (2) Is there an influence of work skills on service quality at the Regional Secretariat of Majalengka Regency, (3) Is there an influence of discipline and work skills on service quality at the Regional Secretariat of Majalengka Regency. The research method used in this research is the survey method. Through the census, it is intended that all populations are also sampled because the population is limited and allows researchers to examine all populations using a questionnaire as a data collection tool. explore factors that cannot be revealed in the questionnaire. As a result, discipline and work skills have a significant influence on quality, while attendance has a significant influence, and work skills have a significant influence. Then, based on the results of the study, it shows that the discipline variable has a greater influence on service quality at the Regional Secretariat of Majalengka Regency than the work ability variable. Thus, both discipline and work skills have an influence on service quality at the Regional Secretariat of Majalengka Regency